The Transformation of the Vowel System in African Latin With a Focus on Vowel Mergers as Evidenced in Inscriptions and the Problem of the Dialectal Positioning of Roman Africa - Adamik, Béla (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Present paper intends to explore the process of the transformation of the vowel system as evidenced in the pre-Christian and Christian inscriptions of the Roman provinces Africa Pro-consularis including Numidia and Mauretania Caesariensis. With the help of the LLDB-Database, the phonological profiles of the selected African provinces will be drawn and compared to those of six more territorial units, i.e. Sardinia, Hispania, Gallia, Dalmatia, the city of Rome and Bruttium et Lucania. Then the dialectal position of the selected African provinces will be described by various methods of phonological analysis regarding vocalism in both periods. It will be demonstrated how the selected African provinces did not form a homogeneous dialectological area. The vocalism of Latin in later Africa Proconsularis including Numidia turns out to be of the same type as of the later Latin in Sardinia, while the vocalism of the Latin in later Mauretania Caesariensis might have started to develop toward the eastern or Balkan type of vocalism. Regarding consonantism, especially the b-w merger, later Mauretania Caesariensis shows explicitly different trends from what we see in later Africa Proconsularis.